Pengaruh Kualitas Produk, Kepuasan Pelanggan, Hambatan Beralih Dan Kepercayaan Merek Terhadap Retensi Pelanggan Wardah Kosmetik Di Kabupaten Klaten - Werdaningrum, Amelia Galuh; Ardiyanto, Faizal (Universitas PGRI Yogyakarta, 2020)
This research aims to determine the effect of product quality, customer satisfaction, switching barriers, and brand trust on customer retention. The sample in this research was 116 respondents of Wardah Cosmetics customers from Klaten Regency. This research used one of non probability sampling technique which is purposive sampling method. This study is also using multiple linear regression to analyze the collected data. The results in this research are product quality, customer satisfaction, switching barriers, and brand influence customer retention both partially and simultaneously.